Alexithymic proﬁle as a predictor of personality resilience in middle adultity - Klyshevich, Natalya Yu.; Verbitskaya, Olga N. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The severity of alexithymia was studied in a Belarusian sample of respondents in middle adult. The resilience of the individual during the speciﬁed period of development was determined. Differences in resilience have been found in adults with different alexithymic proﬁles. The highest indicators of resilience were recorded in individuals without alexithymia, the lowest indicators – in individuals with a high level of alexithymia. Signiﬁcant differences were established in the integrative indicator of resilience, as well as in such components as resilience, coping, self-efﬁcacy, regulation of emotions and cognitions, adaptability (ﬂexibility).
Keywords: alexithymia; alexithymic proﬁle; resilience; components of resilience